(3GdCHMGK GdeajOI aj JMUjd GdYbjOIs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3CeG HYO agPg GdQSGdI JTJed Ydi GdeWGdH GdcdGejI hSejfGgG HGdCHMGK GdeajOI ai JMUjd GdYbjOI s
(3BNQgG (B:s
(3aChLH GdJhHg YfO GdUZjQI HGdSeY hdjcf gPG BNQ eG CQOfG PcQg ai gPg GdebOeI Je cJGH GdCHMGK GdeajOI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(599) s
Keywords: (3GdJhMjO hGdedd hGdfMds